Topology - Davis, Sheldon W (Mc Graw Hill Higher Education, 2005)
It is divided into two parts for first- and second-semester topology courses, but the author has built flexibility into the topic coverage to accomodate the different ways the standard topology course is organized at various schools. It is written for undergraduate students, but can also be used with beginning graduate topology courses.This text is part of the Walter Rudin Student Series in Advanced Mathematics